How Gas Generates in Pouch Cells and Affects Consumer Products - Aalund, Ryan; Endreddy, Bhavana; Pecht, Michael (Frontiers in Chemical Engineering, 2022)
Most of today’s consumer electronic products such as cell phones, laptops, and tablets use pouch lithium-ion cells to make the most efficient use of space, compared to cylindrical and prismatic designs. However, eliminating the metal enclosure comes at a cost if the pouch cell swells due to gas generation and damages the product it is contained within. This paper presents various swollen battery examples in consumer products and how companies handle the issues, reviews the mechanisms of the gas generation, and offers solutions to prevent pouch cell swelling from affecting the devices.